Diabetes-induced hyperglycemia impairs male reproductive function: a systematic review. (10th November 2017) - Maresch, Constanze C; Stute, Dina C; Alves, Marco G; Oliveira, Pedro F; de Kretser, David M; Linn, Thomas
Abstract: BACKGROUND: Hyperglycemia can result from a loss of pancreatic beta-cells or a decline in their function leading to decreased insulin secretion or may arise from insulin resistance and variable degrees of inadequate insulin secretion resulting in diabetes and related comorbidities. To date several reviews have addressed the issue of diabetes-related male infertility but most have focused on how metabolic syndrome causes the decline in male fertility. However, a comprehensive overview as to how diabetes-induced hyperglycemia impairs male fertility is missing. Impaired regulation of glucose and the resultant hyperglycemia are major threats to the health of individuals in modern societies especially given the rapidly rising prevalence affecting an increasing number of men in their reproductive years. Consequently, diabetes-induced hyperglycemia is likely to contribute to a decline in global birth rates especially in those societies with a high diabetic prevalence. OBJECTIVE AND RATIONALE: This systematic review addresses and summarizes the impact of hyperglycemia on male reproductive health with a particular emphasis on the molecular mechanisms that influence the testis and other parts of the male reproductive tract. SEARCH METHODS: A systematic search of the literature published in the MEDLINE-Pubmed database (http://www.ncbi.nlm.nih.gov/pubmed ) and Cochrane Library (http://www.cochranelibrary.com ) was performed, as well as hand searching reference lists, from the earliest available online indexing year until May 2017, using diabetes- and male fertility-related keywords in combination with other search phrases relevant to the topic of hyperglycemia. Inclusion criteria were: clinical studies on type 1 diabetic (T1D) men and studies on T1D animal models with a focus on reproductive parameters. Case reports/series, observational studies and clinical trials were included. Studies on patients with type 2 diabetes (T2D) or animal models of T2D were excluded to distinguish hyperglycemia from other metabolic effects. OUTCOMES: A total of 890 articles were identified of which 197 (32 clinical, 165 animal studies) were selected for qualitative analysis. While the clinical data from men with hyperglycemia-induced reproductive dysfunction were reported in most studies on T1D, the study designs were variable and lacked complete information on patients. Moreover, only a few studies (and mostly animal studies) addressed the underlying mechanisms of how hyperglycemia induces infertility. Potential causes included impaired function of the hypothalamic-pituitary-gonadal axis, increased DNA damage, perturbations in the system of advanced glycation endproducts and their receptor, oxidative stress, increased endoplasmatic reticulum stress, modulation of cellular pathways, impaired mitochondrial function and disrupted sympathetic innervation. However, intervention studies to identify and confirm the pathological mechanisms were missing: data that are essential in understanding these interactions. WIDER IMPLICATIONS: While the effects of regulating the hyperglycemia by the use of insulin and other modulators of glucose metabolism have been reported, more clinical trials providing high quality evidence and specifically addressing the beneficial effects on male reproduction are required. We conclude that interventions using insulin to restore normoglycemia should be a feasible approach to assess the proposed underlying mechanisms of infertility.